Influence of Sales Promotion and Direct Marketing on Decisions to Purchase Services at PT Link Pasipik Indonusa Semarang - Rizky, Angghi Artha; Kurniani, Kurniani -; Poerbo, Suryadi - (Politeknik Negeri Semarang, 2023)
The area around the prot forms an ecosystem for companies supporting export-import activities, especially freight forwarding. The competitive environment requires freight forwarding business acotrs to develop accurate strategies to increase company sales. There was a decline in sales at PT Link Pasipik Indonusa Semarang during 2021-2022. Effort that have been made to increase sales are by Sales Promotion and Direct Marketing.This study aims to explain the effect of Sales Promotion and Direct Marketing on Purchase Decisions for services at PT Link Pasipik Indonusa Semarang. Respondents in this study were 75 service users of PT Link Pasipik Indonusa Semarang. Data collection methods used are observation, interviews, questionnaires, and literature study. This Study uses mutltiple regression analysis with the help of SPSS 26 software. Methods of data analysis using multiple linear regression analysis. The result of this study Sales Promotion and Direct Marketing variables have a positive and significant effect both partially and simultaneously on purchasing decisions. The result of the coefficient of determination (R2) of 0.51 means that Sales Promotion and Direct Marketing contribute 51% to Purchasing Decisions and the remaining 49% is influenced by other variables not examined in this study